I Improving Student Learning Outcomes Of Class VIII A At SMP Negeri 5 Kendari (Junior High School) In English Learning Through NHT (Numbered Heads Together)Cooperative Learning Model - Asni Isnawati (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
The purpose of this study is the NHT (Numbered Head Together) cooperative learning model in English learning can improve student learning outcomes in class VIII-A SMP Negeri 5 Kendari. Classroom action research with the following activity stages: 1) planning, 2) implementing the action, 3) implementing observation and evaluation, and 4) reflection. The results of the research in the two learning cycles are as follows: 1) the observation results of the teacher's ability to manage learning in the second cycle of 12 observation aspects, there are 12 aspects (100%) achieving the criteria of Good (B) and Very Good (SB), there is an increase in the percentage when compared to the results Observations of the teacher's ability to manage learning in the first cycle there were 9 aspects (75%) achieving good (B) and very good (SB) criteria, 2) the results of observing student activeness in learning in the second cycle of 5 observation aspects there were 5 aspects (100%) achieving active (A) and very active (SA) criteria, there is an increase in the percentage when compared to the results of observations of student activeness in learning in the first cycle there are 4 aspects (80%) achieving active criteria (A), and 3) learning outcomes achieved by students showed a very significant increase, where in the second cycle there was an increase in the number of students who got a score of ≥ 70, a total of 27 students (84.4%), The increase in value when compared to the first cycle was 20 students (62.5%) who scored ≥ 70. The NHT (Numbered Head Together) type of cooperative learning model in English subjects can improve learning outcomes for class VIII-A students of SMP Negeri 5 Kendari.